Image de l’espace ou espace de l’image ? - Vasiliki Zachari (Cahiers Mondes Anciens)
The present article proposes an analysis of vases where an altar is associated with a herm, because both of them have an important spatial connection, in view of their installation on the ground. By describing and analysing some vases of Attic production, we will explore how the image’s space is organised on the following cases: when no-one is present (empty space), when the space is established by a frame or not (open space and enclosed space), and the different ways of association of the altar with the herm on the vase (spatial organisation of the vase). Based on the analysis of how these features organise the picture’s space, we will try to understand the construction and nature of space evoked in these scenes.